Validation and longitudinal application of the WHOQOL-HIV questionnaire among people living with HIV and AIDS in Limpopo Province, South Africa - Igumbor, Jude Ofuzinim (My University, 2012)
The rate of HIV infection in South Africa remains high despite the continued efforts to prevent its transmission. Conversely, the rate of AIDS related mortality has been on the decline since the country introduced its comprehensive care and treatment plan. Among other things, the comprehensive plan seeks to coordinate activities to prevent further infection and facilitate health and social support services for the infected and affected. Despite this, South Africa has an increasing number of people living with HIV (PLWH) and is home to the largest population of HIV infected people in the world. Consequently, there is a growing shift of focus of HIV/AIDS response programmes from issues of survival and death prevention to the quality of survival of PLWH. This point accentuates the need for patient evaluation of their wellbeing and quality of life in the context of the country’s HIV/AIDS response services. There are HIV-specific quality of life assessment tools like the WHOQOL-HIV, but these tools are subject to cultural variations and have not been validated across South Africa’s multicultural society. The available tools are often too long and cannot be used in routine care and support of PLWH. In the absence of validated and efficient quality of life assessment tools, there is over reliance on biomedical markers of HIV/AIDS like the CD4 cell count and viral load. These biomedical indicators do not provide a complete view of the impact of the disease given the multidimensional consequences of HIV and AIDS. With the above background, this study sought to firstly explore the health related quality of life (HRQOL) and the experiences of PLWH in seeking care and support services, and secondly, to validate the ability of the WHOQOL-HIV instrument to measure the health related quality of life of PLWH among the three cultural groups in Limpopo Province over a specified time period. The study was divided into two, with the first and second studies using qualitative and quantitative research approaches respectively. Both studies divided their participants into three groups, with each group representing each of the three main ethnic groups in Limpopo Province (Pedi, Tsonga and Venda). The qualitative study used focus group discussions (FGDs) iii to solicit information and grounded theory to guide its participant selection, number of FGDs conducted and the interpretation of its findings. The second study was a longitudinal follow up of participants in the three groups from the point of treatment initiation over 12 months. In the second study, there were three points of data collection (baseline, six and twelve months). The participants were conveniently selected and interviewed repeatedly with the WHOQOL-HIV and MOS-HIV instruments. The study findings were mostly presented in tables and t-tests and ANOVA were used to compare quality of life scores in different groupings while correlation and limits of agreements were used to establish instrument validity. Item-total correlation coefficient and alpha if item deleted, was used to explore the possibility of shortening the WHOQOL-HIV instrument in an attempt to suggest a shorter and more user friendly version of the instrument. The key findings of the qualitative study are that the quality of life of PLWH in Limpopo is determined by three groups of factors (physical, mental and external). The frequency and severity of these factors are determined by the participants’ duration on treatment, disclosure of their HIV status and socioeconomic status. The physical factors were mostly constituted by biological symptoms of the disease. The most commonly cited symptoms were diarrhoea, pain and fatigue. The study also noted marked differences in the occurrence of the symptoms through the trajectory of the disease revealing four main stages: pre-treatment; treatment initiation; early treatment; and treatment maintenance stages. The study also noted that the impact of the determinants of the quality of life on an individual is influenced by intervening factors which can be altered by a set of modifying factors. In all, the quality of life determinants identified by this study replicates those that constitute the WHOQOL-HIV instrument. This finding hence obviates the need for the modification of existing quality of life instruments to suit the three South African ethnic groups investigated by this study. The quantitative study showed high reliability of the WHOQOL-HIV among the three ethnic groups with alpha ranging from 0.79 to 0.94 in the six domains of the instrument. The study iv also showed that the quality of life varied by socio-demographic characteristics such as ethnic group, sex, marital status, number of children, employment status and membership of HIV/AIDS support groups. The observed difference reflects poor financial capacity and activity tolerance across the various categories of the participants and at different times. While significant changes in the quality of life was noted between the baseline data and the six and twelve months data respectively, little or no improvements were seen between the six and twelve months data. The participants were actually more likely to have a better quality of life at six months when compared to their quality of life at twelve months. In the same manner, the median CD4 cell count and viral load were very similar at six and twelve months but differed significantly with the baseline reports. Over time and across cultural groups, the participants reported lower quality of life in the level of dependence domain and financial support subscale. There were little or no associations between the biomedical markers and HRQOL indicators. In addition, the quality of life tended to increase with increase in CD4 cell count. The validation of the WHOQOL-HIV using the MOS-HIV through a correlation of similar domains and their limits of agreement largely suggests that the WHOQOL-HIV is valid but both instruments are not exact replicas in their measurements. The multidimensional nature hypothesized by the original WHOQOL-HIV instrument study was also demonstrated by the factor analysis component matrix. Attempts to shorten the WHOQOL-HIV proved to be impossible as the items with highest item-total correlation varied with the participants’ duration on treatment. In conclusion, this study suggested the needs and factors that contribute to the quality of life of PLWH in Limpopo and how those factors can be harnessed through a set of modifying factors. With this, an individual’s quality of life is determined by the delicate balance between intervening and modifying factors. The linkages between the observed determinants of quality of life suggest a vicious circle where one determinant may exacerbate the effect of another determinant. The study also showed that the WHOQOL-HIV instrument is valid and reliable in measuring the quality of life of PLWH in the province. The observed poor to no associations between the health related quality of life indicators and the biomedical makers show that they cannot be direct proxies of each other. Finally, the study discourages any further shortening of v the WHOQOL-HIV instrument on the basis that HIV-infected people are not a homogenous group as their bio-psychosocial needs vary with time and their position along the trajectory of the disease.
Ph.D., Faculty of health Sciences, University of the Witwatersrand, 2011
Keywords: Acquired Immunodeficiency Diseae; HIV